(untitled) (Research, Society and Development, 2021)
The extraction of aggregates for civil construction in the Vale do Rio Tijucas / SC began around 1900, and has, in more recent times, caused a series of social and environmental impacts, causing conflicts of the type ’proximity’ to emerge. Conflicts of Proximity is a theory or methodology developed by the French geographer Patrice Melé that characterizes a certain type of social conflict where aspects of its effects are valued, having been elaborated four hypotheses of production of these conflicts, namely: process of territorialization, process of transactions social, construction of an intermediate public space and process of local updating of the law. In this article we seek to verify whether these hypotheses can be applied to conflicts in the Vale do Rio Tijucas region. The methodology included bibliographic review, field trips and interviews. We conclude that the French methodology is applied in the Brazilian case study presented, and may eventually be used in other cases in our country.